2022
DOI: 10.1111/ele.14148
|View full text |Cite
|
Sign up to set email alerts
|

Defining null expectations for animal site fidelity

Abstract: Site fidelity—the tendency to return to previously visited locations—is widespread across taxa. Returns may be driven by several mechanisms, including memory, habitat selection, or chance; however, pattern‐based definitions group different generating mechanisms under the same label of ‘site fidelity’, often assuming memory as the main driver. We propose an operational definition of site fidelity as patterns of return that deviate from a null expectation derived from a memory‐free movement model. First, using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…On the one hand, we might expect mild to moderate collinearity between familiarity covariates and other important environmental drivers, which can make it challenging to quantify their unique contributions (Picardi et al, 2023). On the other hand, accounting for familiarity and memory effects should reduce bias associated with estimators of habitat-selection strength.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, we might expect mild to moderate collinearity between familiarity covariates and other important environmental drivers, which can make it challenging to quantify their unique contributions (Picardi et al, 2023). On the other hand, accounting for familiarity and memory effects should reduce bias associated with estimators of habitat-selection strength.…”
Section: Discussionmentioning
confidence: 99%
“…A notable limitation of this approach is the risk of overestimating the importance of familiarity due to unaccounted-for habitat attributes (e.g. if the OD reflects the distribution of an unobserved resource; see Picardi et al 2023). The OD approach further necessitates that users choose an appropriate time window in the past for calculating the OD (Figure 1).…”
Section: Exploring How Memory Influences Animal Movements Using Ssasmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our case study, one can evaluate whether the observed and simulated paths exhibit similar behaviour near roads, rivers, or other prominent environmental features. Second, our simulator can be used as a way to develop a null distribution to test for evidence of site fidelity and/or memory (Picardi et al., 2023). One can, for example, simulate movement in the absence of home‐ranging behaviour and/or absence of habitat selection and contrast emerging patterns with more complex models.…”
Section: Discussionmentioning
confidence: 99%
“…The residuals for the final model were evaluated with the "DHARMa" package (Hartig & Hartig, 2017). We used the "fidelity" package in R (Picardi et al, 2023) to estimate site fidelity on the basis of the Blischke-Scheuer method-of-moments estimator, which calculates the step length parameters of shape and scale for a comparison with simulated toad movements according to a Correlated Random Walk (CRW). We included every toad with 3 or more relocations after the removal of the initial capture points in this analysis.…”
Section: Distance Movedmentioning
confidence: 99%